PENGARUH PENDIDIKAN KEWIRAUSAHAAN DAN DUKUNGAN INSTITUSIONAL UNIVERSITAS TERHADAP NIAT BERWIRAUSAHA DENGAN EFIKASI DIRI SEBAGAI VARIABLE MEDIASI PADA MAHASISWA FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS ANDALAS - Dianthadhisa Agusti Putri; Harif Amali Rivai; Donard Games (Halu Oleo University, 2025)
This study aims to analyse the influence of entrepreneurship education and institutional support from universities on entrepreneurial intention, with self-efficacy as a mediating variable among students at the Faculty of Economics and Business, Andalas University. This study uses a quantitative approach with the Structural Equation Modelling (SEM) method through SmartPLS 3.0 to test the proposed hypotheses. Data were collected from 221 active students at the Faculty of Economics and Business, University of Andalas. The results indicate that entrepreneurship education has a positive influence on entrepreneurial intention, as well as a positive influence on self-efficacy, which in turn enhances entrepreneurial intention. However, institutional support does not significantly influence entrepreneurial intention or self-efficacy, indicating that institutional support alone is insufficient to enhance students' entrepreneurial intention. Additionally, this study confirms that self-efficacy mediates the influence of entrepreneurship education on entrepreneurial intention, emphasising the importance of fostering students' self-confidence through education. This study contributes to the understanding of the factors influencing students' entrepreneurial decisions and highlights the importance of a more comprehensive approach in entrepreneurship education and institutional support in higher education.